Depleting Trim28 in adult mice is well tolerated and reduces levels of α-synuclein and tau - Maxime WC Rousseaux; Jean-Pierre Revelli; Gabriel E Vázquez-Vélez; Ji-Yoen Kim; Evelyn Craigen; Kristyn Gonzales; Jaclyn Beckinghausen; Huda Y Zoghbi (eLife, 2018)
Alzheimer's and Parkinson's disease are late onset neurodegenerative diseases that will require therapy over decades to mitigate the effects of disease-driving proteins such tau and α-synuclein (α-Syn). Previously we found that TRIM28 regulates the levels and toxicity of α-Syn and tau (Rousseaux et al., 2016). However, it was not clear how TRIM28 regulates α-Syn and it was not known if its chronic inhibition later in life was safe. Here, we show that TRIM28 may regulate α-Syn and tau levels via SUMOylation, and that genetic suppression of Trim28 in adult mice is compatible with life. We were surprised to see that mice lacking Trim28 in adulthood do not exhibit behavioral or pathological phenotypes, and importantly, adult reduction of TRIM28 results in a decrease of α-Syn and tau levels. These results suggest that deleterious effects from TRIM28 depletion are limited to development and that its inhibition adulthood provides a potential path for modulating α-Syn and tau levels.